Reproductive Biology of Mystacoleucus padangensis in Waters Naborsahan River and Toba Lake Tobasa Regency Province North Sumatra - Helperida Gurning; Chaidir Pulungan; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research about reproductive biology of pora-pora (Mystacoleucus padangensis) doneon January to April 2014 in Naborsahan river and Toba Lake. The aim of the researchwas to difine male and female morfology fish, sex ratio, maturity level, fecundity value,relatim ship of fecundity with length and weight. The method in the research was surveymethod. The sampling was done at three stations, namely in Naborsahan river (Station I),downstream of Naborsahan river (Station II), and Toba Lake (Stasiun III). The resultsshow from 515 fishes (189 male and 326 female). The result shown of male and femalewas 1:1,8. The indeks Gonad Somatic (IGS) of the male fish was 1,4-12,8% and thefemale was 0,5-19,6%. Egg diameter was 0,3-0,8 mm. The fecundity equality were20.227-173.441. The relatim ship of fecundity with lenght Y= -14221+2182X and therelatim ship equality of fecundity with weight Y= -402,5+2558X.Keyword: Mystacoleucus padangensis, maturity level, fecundity, GSI